(untitled) (Progressive Agriculture, 2014)
An experiment was conducted for a period of 135 days on the effect of duckweed (Lemna minor) as supplementary feed on monoculture of GIFT strain of tilapia (Oreochromis niloticus). The experiment had two treatments, each with three replications. In treatment-1 ponds were supplied with duckweed as supplementary fish feed and in treatment-2 ponds were kept as control (without supply of duckweed). Ponds were stocked at a stocking density of 150 fingerlings per decimal. The ponds were fertilized fortnightly with poultry dropping at the rate of 5 kg/decimal, urea 60g/decimal and TSP 90g/decimal. Duckweeds were supplied to the ponds (treatment-1) at the rate of 60% of the total body weight (wet weight basis) of the fish. During the experimental period, the ranges of physico-chemical parameters viz, water temperature, transparency, dissolved oxygen, pH, total alkalinity, free CO2, PO4-P, and NO3-N were within the productive limit and more or less similar in all the ponds under treatments 1 and 2. There were 24 genera of phytoplankton under 5 major groups and 10 genera of zooplankton under 3 major groups were found in the experimental ponds. Mean survival rates in treatments 1 and 2 were 85.34% and 83.68% respectively. Specific growth rate (SGR, % per day) of the fish in treatments 1 and 2 were 1.90% and 1.60% respectively. Calculated net production of the fish in treatment-1 was 5.03 ton/ha/yr and in treatment-2 was 3.11 ton/ha/yr. By t test it was found that the net production of fish in treatment-1 was significantly (p<0.05) higher than that of treatment-2. DOI: http://dx.doi.org/10.3329/pa.v18i2.18201 Progress. Agric. 18(2): 183 - 188, 2007